Incidence and clinical and immunological characteristics of primary Toxoplasma gondii infection in HIV-infected patients - Machala, Ladislav; Malý, Marek; Beran, Ondřej; Jilich, David; Kodym, Petr (International journal of infectious diseases, 2013)
OBJECTIVES: To determine the incidence and laboratory characteristics of primary Toxoplasma gondii infection in HIV-infected individuals. METHODS: This retrospective study was conducted between 1988 and 2012 on a cohort of 1130 HIV-infected patients at the AIDS Center Prague. Toxoplasma serology, standard laboratory parameters, and health status were evaluated at 3-6-month intervals for all patients. RESULTS: The total person-time of follow-up of patients at risk of Toxoplasma seroconversion was 3046.3 years; there were 14 primary T. gondii infections, yielding an incidence rate of 0.0046 (95% confidence interval 0.0027-0.0078). Most of the subjects were clinically asymptomatic, but in one case seroconversion was accompanied by transient cervical lymphadenopathy. The CD4+ T-lymphocyte count geometric mean increased from 418 (95% confidence interval 303-579) cells/μl before seroconversion to 501 (95% confidence interval 363-691) cells/μl after seroconversion (p = 0.004), while other parameters (CD8+ T-lymphocytes, natural killer cells, viral load, beta2-microglobulin, total immunoglobulins) remained unchanged. As compared to the control group, patients with primary toxoplasmosis had higher initial levels of total immunoglobulins IgA and IgG and a tendency to higher CD8+ T lymphocyte counts. CONCLUSIONS: Neither the incidence nor the course of the primary Toxoplasma infection was influenced by the immune status of the patients. Immune parameters of patients with primary Toxoplasma infection did not differ from those of the controls.
Keywords: HIV; Young Adult; Male; retrospektivní studie; AIDS-Related Opportunistic Infections; mladý dospělý; oportunní infekce doprovázející AIDS; HIV séropozitivita; Toxoplasma gondii; Adult; dospělí; toxoplazmóza; mužské pohlaví; incidence; Primary infection; CD4 Lymphocyte Count; počet CD4 lymfocytů; HIV protilátky; HIV Antibodies; lidé; Toxoplasmosis; ženské pohlaví; Humans; Seroconversion; Retrospective Studies; Female; HIV Seropositivity; lidé středního věku; Incidence; Middle Aged